(3QSGdI GdJHjjf hGdGSJOQGc dHYV eGde JOQcg GdYbhd aj cTa GdcaQ GdeMLhH ef GdEdMGO hGdETQGcs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce eDRd GdCRd hJhSdJ Edjg Hhdjg GdbGFe GdgGOi YdI GdYdd s
(3BNQgG (B:s
(3hjhVM Cfge NGdahG CeQ GdHGQi hNQLhG Yf Sff GdJhMjO hGdOjf dcf Nai Yf Cee GdTQc cdGe GdeYHhO JeJ HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B70s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis